2020
DOI: 10.37394/232013.2020.15.2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Angular Momentum and Ostrogradsky-Gauss Theorem in the Equations of Mechanics

Abstract: There are many experimental facts that currently cannot be described theoretically. A possible reason is bad mathematical models and algorithms for calculation, despite the many works in this area of research. The aim of this work is to clarificate the mathematical models of describing for rarefied gas and continuous mechanics and to study the errors that arise when we describe a rarefied gas through distribution function. Writing physical values conservation laws via delta functions, the same classical defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…An important component of research is the choice of model. Previous works have shown that classical models do not include one of the most important laws-the law of conservation of angular momentum, if the moment does not act as a given force effect [1]- [6]. When the action of the distributed moment is taken into account, the system of equations is supplemented by the moment conservation law.…”
Section: Introductionmentioning
confidence: 99%
“…An important component of research is the choice of model. Previous works have shown that classical models do not include one of the most important laws-the law of conservation of angular momentum, if the moment does not act as a given force effect [1]- [6]. When the action of the distributed moment is taken into account, the system of equations is supplemented by the moment conservation law.…”
Section: Introductionmentioning
confidence: 99%